Silver paste composition and preparation method and application thereof

By using nano- and micro-grade silver powder, metal precursor and non-precious metal additives in the silver paste composition, low-temperature and low-pressure sintering is achieved, and the problems of poor morphology, poor conductivity and adhesion in the prior art are solved. , a denser and better conductive silver glue layer is formed, improving application stability and reliability.

CN119495464APending Publication Date: 2025-02-21DK ELECTRONICS MATERIALS INC
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411628822.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The silver paste composition in the prior art is poor in sintering to form the silver glue layer, has poor conductivity and adhesion, and is prone to curling deformation of the substrate and chip, chip micro-cracking, and insufficient adhesion of the silver glue layer. , leading to short circuits and pollution problems.

Method used

A silver paste composition is used, which comprises 80 to 120 parts of silver-containing filler, 20 to 40 parts of organic solvent, 5 to 15 parts of non-precious metal additives, and 8 to 10 parts of peroxide organic additives As well as 1 to 5 parts of rheological agent, the combination of nano-scale and micro-scale silver powder, metal precursor and non-precious metal additives can achieve low temperature and low pressure sintering to form a denser and more conductive silver glue layer.

Benefits of technology

The better morphology, denser structure, higher conductivity and adhesion of the silver glue layer is achieved, the porosity is reduced, and the application stability and reliability of the silver paste composition are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495464A_ABST
    Figure CN119495464A_ABST
Patent Text Reader

Abstract

The invention provides a silver paste composition and a preparation method and application thereof. The silver paste composition comprises the following components in parts by weight: 80-120 parts of silver-containing filler, 20-40 parts of an organic solvent, 5-15 parts of a non-noble metal auxiliary agent with an atomic number of 24-30, 8-10 parts of a peroxide organic auxiliary agent and 1-5 parts of a rheological agent, the silver-containing filler comprises elemental silver powder and a silver-containing compound, and the weight ratio of the elemental silver powder to the silver-containing compound is (18-20): 1; the elemental silver powder comprises micron-scale silver powder and nano-scale silver powder; the silver-containing compound is selected from one or more of silver carbonate, silver lactate, silver formate, silver citrate and silver oxide. According to the low-temperature pressure sintered silver paste composition, low-temperature and low-pressure sintering of the silver paste composition is achieved by adding nano-scale and micron-scale silver powder, a metal precursor, a non-noble metal auxiliary agent and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic packaging, and in particular to a silver paste composition, a preparation method and application thereof. Background Art

[0002] Traditional insulated gate bipolar transistors (IGBT modules) are manufactured by soldering, that is, using solder paste or preformed solder film, which is melted and solidified into solder alloy through the reflow process to connect the chip and substrate in the power module. The modules manufactured by this method have the disadvantages of short life and poor heat dissipation, and due to the low melting point of the solder, the junction temperature of the chip in the module is limited to below 150°C. In view of this point, pressurized sintered silver paste is a good substitute for welding materials.

[0003] However, the existing press-sintered silver paste has problems such as poor density and high porosity after sintering. At the same time, in the process of sintering to form the silver paste layer, the sintering temperature and pressure are both high, which easily causes the substrate and chip to warp and deform, and the chip to crack. In addition, there are also problems such as the poor adhesion of the silver paste around the chip that is not pressed, easy to fall off, and easy to cause short circuits and pollution, which seriously affects its application effect.

[0004] Based on this, how to design a new silver paste composition so that the bonding silver glue layer formed after sintering can have better morphology, be denser, have fewer defects, and at the same time have better conductivity and stronger adhesion is one of the important technical problems that need to be solved in this field. Summary of the invention

[0005] The main purpose of the present invention is to provide a silver paste composition, a preparation method and application thereof, so as to solve the problems of poor morphology, poor conductivity and poor adhesion of the silver paste composition in the prior art when sintering and forming a bonding silver glue layer.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a silver paste composition, which comprises, by weight: 80 to 120 parts of a silver-containing filler, 20 to 40 parts of an organic solvent, 5 to 15 parts of a non-precious metal additive with an atomic number of 24 to 30, 8 to 10 parts of a peroxide organic additive and 1 to 5 parts of a rheological agent; the silver-containing filler comprises elemental silver powder and a silver-containing compound, and the weight ratio of the elemental silver powder to the silver-containing compound is (18 to 20):1; the elemental silver powder comprises micron-sized silver powder and nano-sized silver powder; the silver-containing compound is selected from one or more of silver carbonate, silver lactate, silver formate, silver citrate and silver oxide.

[0007] Furthermore, the micron-sized silver powder is in the form of flakes, and the flake diameter of the micron-sized silver powder is 1 μm to 8 μm; the nano-sized silver powder is in the form of spheres, and the particle diameter of the nano-sized silver powder is 200 nm to 500 nm; preferably, the weight ratio of the micron-sized silver powder to the nano-sized silver powder is (2 to 3):1.

[0008] Further, the organic solvent is selected from one or more of aromatic compounds, ketone compounds, aliphatic ester compounds, alcohol ether compounds, ether compounds, halogenated hydrocarbon compounds, glycol compounds, alcohol compounds and terpene compounds; preferably, the organic solvent is selected from terpineol, ethylene glycol monobutyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, DBE, propylene glycol monopropyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ... One or more of alcohol monoethyl ether and tripropylene glycol monopropyl ether; preferably, the organic solvent is selected from one or more of pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE; more preferably, the organic solvent is selected from a mixed solvent formed by pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE, and in the mixed solvent, the weight ratio of pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE is (5-6): (1-2): (2-3): 1.

[0009] Furthermore, the non-precious metal additive with an atomic number of 24 to 30 is copper powder and / or nickel powder; and / or the peroxide organic additive is selected from one or more of 1,1,3,3-tetramethylbutyl peroxyneodecanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, isopropyl peroxyneodecanoate, di-n-propyl peroxydicarbonate, tert-amyl peroxyneodecanoate and di-(3,5,5-trimethylhexanoyl)-peroxide; preferably, the copper powder and the nickel powder are both spherical, and the particle size of the copper powder and the nickel powder are each independently 1 μm to 5 μm.

[0010] Furthermore, the rheological agent is selected from one or more of methyl cellulose, ethyl cellulose, ethyl methyl cellulose, carboxy cellulose, polytetrafluoroethylene wax, polyamide wax and hydrogenated castor oil; preferably, the rheological agent is ethyl cellulose and / or polytetrafluoroethylene wax; more preferably, the rheological agent is a mixture of ethyl cellulose and polytetrafluoroethylene wax, and the weight ratio of ethyl cellulose to polytetrafluoroethylene wax in the mixture is (3-4):1.

[0011] The second aspect of the present invention provides a method for preparing the above-mentioned silver paste composition, comprising: step S1, mixing the rheological agent to be activated with the first organic solvent, and obtaining the rheological agent after activation; step S2, mixing the rheological agent with the second organic solvent, and obtaining a first mixed solution after a first stirring; step S3, adding a non-precious metal additive with an atomic number of 24 to 30 to the first mixed solution, and obtaining a second mixed solution after a second stirring; step S4, adding a silver-containing filler to the second mixed solution, and obtaining a third mixed solution after a third stirring; step S5, adding a peroxide organic additive to the third mixed solution, and obtaining a silver paste composition after dispersion, filtration and degassing.

[0012] Furthermore, the activation temperature is 60°C to 65°C, and the activation time is 30min to 60min.

[0013] Furthermore, in step S1, the weight ratio of the rheological agent to be activated to the first organic solvent is 1:(2.8-3.2).

[0014] Further, the rotation speeds of the first stirring and the second stirring are independently 1000 rpm to 1400 rpm, and the durations are independently 1 min to 2 min; and / or, the rotation speed of the third stirring is 1500 rpm to 2000 rpm, and the duration is 3 min to 5 min.

[0015] The third aspect of the present invention provides an application of the silver paste composition as a chip packaging material in the field of electronic devices and semiconductor devices.

[0016] The technical solution of the present invention provides a low-temperature pressure-sintered silver paste composition, wherein low-temperature and low-pressure sintering of the silver paste composition is achieved by adding nano- and micron-sized silver powders, metal precursors, and non-precious metal additives. The silver paste layer formed by the obtained silver paste composition after sintering has good bonding performance and conductivity, and its structure is more compact and the porosity is lower, thereby showing higher bonding performance and safety reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 This is a scanning electron microscope photograph of the cross section of the glue layer obtained after the silver paste composition in Example 1 forms a silver glue layer and slices it, with a magnification of 2k;

[0019] Figure 2 This is a scanning electron microscope photograph of the cross section of the glue layer obtained after the silver paste composition in Example 1 forms a silver glue layer and slices it, with a magnification of 1k;

[0020] Figure 3 This is a scanning electron microscope photograph of the cross section of the glue layer obtained after the silver paste composition in Comparative Example 1 forms a silver glue layer and slices it, with a magnification of 3k;

[0021] Figure 4 This is a scanning electron microscope photograph of the cross section of the glue layer obtained after the silver paste composition in Comparative Example 1 forms a silver glue layer and slices it, with a magnification of 1.5k. DETAILED DESCRIPTION

[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0023] As described in the background art, the silver paste composition in the prior art has the problems of poor morphology, poor conductivity and poor adhesion when sintering and forming a bonding silver glue layer. In order to solve the above technical problems, the first aspect of the present invention provides a silver paste composition, which comprises, by weight: 80 to 120 parts of silver-containing filler, 20 to 40 parts of organic solvent, 5 to 15 parts of non-precious metal additives with atomic numbers of 24 to 30, 8 to 10 parts of peroxide organic additives and 1 to 5 parts of rheological agent; the silver-containing filler comprises elemental silver powder and silver-containing compound, and the weight ratio of elemental silver powder to silver-containing compound is (18 to 20): 1; the elemental silver powder comprises micron-sized silver powder and nano-sized silver powder; the silver-containing compound is selected from one or more of silver carbonate, silver lactate, silver formate, silver citrate and silver oxide.

[0024] The present invention simultaneously uses micron-sized silver powder and nano-sized silver powder, silver-containing compounds, and non-precious metal additives with atomic numbers of 24 to 30 as components of the silver paste composition, and strictly controls the weight ratio of each component, thereby obtaining a silver paste composition capable of low-temperature and low-pressure sintering. Compared with a silver paste composition containing only pure micron-sized silver powder, the above-mentioned silver paste composition contains both micron-sized silver powder and nano-sized silver powder, wherein the micron-sized silver powder can be well combined with the substrate during the application process, and the nano-sized silver powder is easier to sinter at low temperature. The two powders fill each other during sintering to ensure the compactness of the glue layer, thereby increasing the fluidity of the silver paste composition while effectively improving its conductivity and mechanical strength after sintering and curing. In particular, the above-mentioned silver paste composition also includes a special silver-containing compound, i.e., a metal precursor, which can be decomposed in the subsequent sintering process to obtain a finer size of metallic silver nano-single substance, so that the silver paste composition forms a denser silver glue layer after sintering and curing, effectively improving adhesion and reducing resistivity.

[0025] In particular, the silver-containing compound is preferably selected from one or more of silver carbonate, silver lactate, silver formate, silver citrate and silver oxide, and its weight ratio to the elemental silver powder is precisely controlled, so that during sintering, the silver-containing precursor and the dispersant on the surface of the elemental silver powder (which is a conventional organic additive added during the production of silver powder, generally including stearic acid, fatty acid salts and fatty acid esters, etc.) can undergo a reduction reaction, and then decompose and fuse into silver nanoparticles, so as to further optimize the sintering and curing process of the silver paste composition, reduce the porosity, form a denser, more uniform and more adhesive silver layer, and improve its stability and reliability during application.

[0026] In several preferred embodiments, the micron-sized silver powder is in the form of flakes, and the flake diameter of the micron-sized silver powder is 1 μm to 8 μm, preferably 4 μm to 6 μm, such as 4.5 μm, 5.0 μm, 5.5 μm, and 6.0 μm; the nano-sized silver powder is in the form of a sphere, and the particle diameter of the nano-sized silver powder is 200 nm to 500 nm, preferably 300 nm to 450 nm, such as 300 nm, 350 nm, 400 nm, and 450 nm. The mixed use of the flake silver powder and the spherical silver powder with the above-mentioned size characteristics can better cooperate and significantly improve the rheological properties of the silver paste composition, making it more uniform during printing and coating, thereby obtaining a more uniform, dense, and highly adhesive silver paste layer.

[0027] After a large number of experiments, the inventors have found that the weight ratio of micron-sized silver powder to nano-sized silver powder is preferably (2-3):1, so that the silver paste composition can form a highly conductive silver layer while showing good fluidity.

[0028] Further, the organic solvent is selected from one or more of aromatic compounds, ketone compounds, aliphatic ester compounds, alcohol ether compounds, ether compounds, halogenated hydrocarbon compounds, glycol compounds, alcohol compounds and terpene compounds. In practical applications, the preferred organic solvent is selected from one or more of terpineol, ethylene glycol monobutyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, DBE, propylene glycol monopropyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether and tripropylene glycol monopropyl ether. The selection of the above-mentioned organic solvent can balance the stability and viscosity of the obtained silver paste composition during printing, coating and curing, thereby optimizing the application process and improving production efficiency.

[0029] Wherein, DBE is a dibasic ester mixture, which is a mixture of three dibasic esters, i.e. a mixture of dimethyl succinate (butanedioate), dimethyl glutarate and dimethyl adipate. The DBE used in the present invention is specifically DBE (dibasic ester mixture) produced by Jinan Deying Chemical Co., Ltd.

[0030] In order to further improve the rheological properties of the silver paste composition, in several preferred embodiments, the organic solvent is selected from one or more of pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE. In several more preferred embodiments, the organic solvent is selected from a mixed solvent formed by pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE, and in the mixed solvent, the weight ratio of pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE is (5-6): (1-2): (2-3): 1. Based on the above-mentioned organic solvent types, the inventor has selected a mixed organic solvent system formed by pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE through a large number of experiments, which can more significantly improve the printability and curing performance of the silver paste, so that the silver paste composition provided by it is more uniform during the printing and coating process, reduces the generation of bubbles and defects, and finally forms a silver glue layer with better bonding strength and denser structure.

[0031] Furthermore, the non-precious metal additive is copper powder and / or nickel powder. The addition of copper powder and / or nickel powder can promote the sintering of the silver paste composition, and at the same time improve its adhesion and conductivity after sintering to obtain the silver glue layer. In several preferred embodiments, the copper powder and the nickel powder are both spherical, and the particle sizes of the copper powder and the nickel powder are independently 1μm to 5μm, preferably 1.5μm to 2.5μm, such as 1.5μm, 1.7μm, 1.9μm, 2.0μm, 2.2μm, and 2.4μm. The spherical copper powder and spherical nickel powder in the above-mentioned particle size range can better cooperate with the elemental silver powder to form a closer contact, thereby improving the conductivity and adhesion of the silver paste composition after sintering and curing.

[0032] In several typical embodiments, the peroxide organic auxiliary is selected from one or more of 1,1,3,3-tetramethylbutyl peroxyneodecanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, isopropyl peroxyneodecanoate, di-n-propyl peroxydicarbonate, tert-amyl peroxyneodecanoate and di-(3,5,5-trimethylhexanoyl)-peroxide.

[0033] In order to more effectively improve the stability and viscosity of the silver paste composition during printing and curing, in several preferred embodiments, the rheological agent is selected from one or more of methyl cellulose, ethyl cellulose, ethyl methyl cellulose, carboxy cellulose, polytetrafluoroethylene wax, polyamide wax and hydrogenated castor oil, and more preferably it is ethyl cellulose and / or polytetrafluoroethylene wax. In several more preferred embodiments, the rheological agent is a mixture of ethyl cellulose and polytetrafluoroethylene wax, and the weight ratio of ethyl cellulose to polytetrafluoroethylene wax in the mixture is (3 to 4): 1. The combined use of the above-mentioned rheological agents can further optimize the rheological properties of the silver paste composition, making it more uniform during the printing process, while reducing the generation of bubbles and defects to a greater extent, and improving the adhesion and reliability of the sintered silver glue layer.

[0034] Furthermore, the silver paste composition provided by the present invention further comprises one or more of a wetting and dispersing agent, a defoaming agent and an anti-settling agent, and the wetting and dispersing agent, the defoaming agent and the anti-settling agent are each independently 0.5 to 1.0 parts by weight. Preferably, the wetting and dispersing agent is BYK330; the defoaming agent is BYK141; and the anti-settling agent is BYK607.

[0035] The second aspect of the present invention provides a method for preparing the above-mentioned silver paste composition, comprising: step S1, mixing the rheological agent to be activated with the first organic solvent, and obtaining the rheological agent after activation; step S2, mixing the rheological agent with the second organic solvent, and obtaining a first mixed solution after a first stirring; step S3, adding a non-precious metal additive with an atomic number of 24 to 30 to the first mixed solution, and obtaining a second mixed solution after a second stirring; step S4, adding a silver-containing filler to the second mixed solution, and obtaining a third mixed solution after a third stirring; step S5, adding a peroxide organic additive to the third mixed solution, and obtaining a silver paste composition after dispersion, filtration and degassing.

[0036] With respect to the above-mentioned silver paste composition, the present invention provides a corresponding preparation method thereof, which not only successfully prepares a silver paste composition with excellent performance, but also simplifies the production process, improves the rheology and stability of the obtained silver paste composition, is suitable for large-scale production, reduces production costs, and improves production efficiency. In particular, the activation treatment of the rheological agent in step S1 stimulates the activity of the material, thereby prompting it to form a network structure, and finally achieves a thixotropic effect, improves the rheological properties of the obtained silver paste composition, and then improves its printing performance during the application process and the structural density after curing.

[0037] Furthermore, the activation temperature is 60°C to 65°C, and the activation time is 30min to 60min. The selection of such activation conditions can make the rheological agent more fully activated, improve its dispersibility and stability in the silver paste composition, thereby optimizing the printing performance of the silver paste composition and the conductive performance of the adhesive layer obtained after sintering and curing.

[0038] In order to further fully dissolve and activate the rheological agent in the organic solvent and improve the rheological properties of the silver paste composition in which it is located, the inventors have conducted a large number of experiments and, in several typical embodiments, preferably in step S1, the weight ratio of the rheological agent to be activated to the first organic solvent is 1: (2.8-3.2). This weight ratio relationship makes the corresponding printing and coating process more uniform, produces fewer bubbles and defects, and thus obtains a silver paste layer with a higher structural density.

[0039] Furthermore, the rotation speeds of the first stirring and the second stirring are independently 1000rpm to 1400rpm, and the time is independently 1min to 2min. The selection of the above-mentioned first stirring and second stirring conditions can make the components more fully mixed and improve the uniformity and stability of the silver paste solvent system. At the same time, it is preferred that the rotation speed of the third stirring is 1500rpm to 2000rpm, and the time is 3min to 5min, so that the silver-containing filler, that is, micron-sized silver powder, nano-sized silver powder and silver-containing compound can be dispersed more evenly in the second mixed solution, thereby further improving the rheological properties of the silver paste composition, as well as the conductive properties and bonding strength of the silver glue layer obtained after sintering and curing.

[0040] The third aspect of the present invention provides an application of the above silver paste composition as a chip packaging material in the field of electronic devices and semiconductor devices. After sintering, the above silver paste composition can form a silver paste layer with excellent conductivity and adhesion. When it is used to connect the substrate and the chip, it can form a connection with good performance, significantly increase the node temperature of the chip, thereby reducing the module's requirements for the heat dissipation system, thereby reducing its related overall manufacturing cost.

[0041] In practical applications, the chip can be selected from one or more of SiC, GaN and IGBT. Taking a 5*5mm SiC chip as an example, after sintering to form a silver glue layer, its thrust is greater than 200 kg, and the resulting silver glue layer is denser and has a lower porosity. Even in the case of pressureless sintering, the bonding strength provided by the silver glue layer can still provide a thrust of tens of kilograms. After pressure sintering, the unpressed part of the silver glue layer around the chip provides a higher adhesion, and the glue layer will not fall off, avoiding problems such as short circuit and contamination during chip operation.

[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0043] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0044] Example 1

[0045] A method for preparing a silver paste composition:

[0046] (1) Weigh 25 g of ethyl cellulose, a rheological agent to be activated, and 75 g of terpineol, an organic solvent, and heat and stir at 65° C. for 1 hour to prepare a semi-finished product A; weigh 25 g of polytetrafluoroethylene wax, a rheological agent to be activated, and 75 g of terpineol, an organic solvent, and heat and stir at 65° C. for 1 hour to prepare a semi-finished product B.

[0047] (2) 0.3 g of diethylene glycol butyl ether acetate, 0.8 g of terpineol, 0.5 g of diethylene glycol butyl ether, and 0.2 g of DBE (purchased from Jinan Deying Chemical) were prepared into a mixed solvent, and then 0.3 g of the semi-finished product A (including 0.075 g of rheological agent ethyl cellulose and 0.225 g of organic solvent terpineol) and 0.1 g of the semi-finished product B (including 0.025 g of rheological agent polytetrafluoroethylene wax and 0.075 g of organic solvent terpineol) in (1) were weighed and added into the obtained mixed solvent, and a first stirring was performed at a speed of 1200 rpm for 2 min using a homogenizer to obtain a first mixed solution, and the temperature was controlled below 40° C. during the stirring process.

[0048] (3) 1.5 g of spherical nickel powder (with a particle size of 2.2 μm), 0.05 g of wetting and dispersing agent BYK330, and 0.05 g of defoaming agent BYK141 were added to the obtained first mixed solution, and a second stirring was performed at a rotation speed of 1200 rpm for 2 min using a homogenizer to obtain a second mixed solution. The temperature was controlled below 40° C. during the stirring process.

[0049] (4) 8.2 g of micron flaky silver powder (with a flake diameter of 5 μm), 3 g of nano spherical silver powder (with a particle diameter of 400 nm), and 0.6 g of a silver-containing compound Ag2CO3 (with a particle diameter of 3 μm) were added to the obtained second mixed solution, and the mixture was stirred for a third time at a rotation speed of 1500 rpm for 5 min using a homogenizer to obtain a third mixed solution. The temperature was controlled below 40° C. during the stirring process.

[0050] (5) Add 0.8 g of 1,1,3,3-tetramethylbutyl peroxyneodecanoate to the obtained third mixed solution, and disperse it three times using a three-roll mill, controlling the temperature below 40° C. during the dispersion process; then filter the dispersed slurry twice using a 500-mesh filter, and then put it into a vacuum degassing machine and vacuum degasse it at room temperature for 10 minutes to obtain a silver paste composition.

[0051] In the obtained silver paste composition, the weight ratio of the silver-containing filler, the organic solvent, the non-precious metal additive, the peroxide organic additive and the rheological agent is 118:21:15:8:1, and wherein:

[0052] In the silver-containing filler, the weight ratio of micron-sized silver powder to nano-sized silver powder is 2.73:1, and the weight ratio of the sum of the weight of the micron-sized silver powder and the nano-sized silver powder, that is, the total weight of the elemental silver powder to the silver-containing compound is 18.67:1;

[0053] In the organic solvent, the weight ratio of pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE is 1.1:0.3:0.5:0.2, i.e. 5.5:1.5:2.5:1;

[0054] In the rheological agent, the weight ratio of ethyl cellulose to polytetrafluoroethylene wax is 3:1.

[0055] Example 2

[0056] A method for preparing a silver paste composition:

[0057] (1) The same as in Example 1.

[0058] (2) 0.3 g of diethylene glycol butyl ether acetate, 0.8 g of terpineol, 0.5 g of diethylene glycol butyl ether, and 0.2 g of DBE are prepared into a mixed solvent, and then 0.4 g of the semi-finished product A in (1) (including 0.1 g of rheological agent ethyl cellulose and 0.3 g of organic solvent terpineol) is weighed and added to the obtained mixed solvent, and a first stirring is performed at a speed of 1000 rpm for 1 min using a homogenizer to obtain a first mixed solution, and the temperature is controlled below 40° C. during the stirring process.

[0059] (3) 1.5 g of spherical nickel powder (with a particle size of 2.2 μm), 0.05 g of wetting and dispersing agent BYK330, 0.05 g of defoaming agent BYK141 and 0.05 g of anti-settling agent BYK607 were added to the obtained first mixed solution, and the mixture was stirred for a second time at a speed of 1000 rpm for 1 min using a homogenizer to obtain a second mixed solution. The temperature was controlled below 40° C. during the stirring process.

[0060] (4) 8.2 g of micron flaky silver powder (with a flake diameter of 5 μm), 3 g of nano spherical silver powder (with a particle diameter of 400 nm), and 0.6 g of a silver-containing compound AgO (with a particle diameter of 3 μm) were added to the obtained second mixed solution, and the mixture was stirred for a third time at a rotation speed of 2000 rpm for 3 min using a homogenizer to obtain a third mixed solution. The temperature was controlled below 40° C. during the stirring process.

[0061] (5) Add 0.8 g of tert-butyl peroxy-2-ethylhexanoate to the obtained third mixed solution, and disperse it three times using a three-roll mill, controlling the temperature below 40° C. during the dispersion process; then filter the dispersed slurry twice using a 500-mesh filter, and then put it into a vacuum degassing machine and vacuum degasse it at room temperature for 10 minutes to obtain a silver paste composition.

[0062] In the obtained silver paste composition, the weight ratio of the silver-containing filler, the organic solvent, the non-precious metal additive, the peroxide organic additive and the rheological agent is 118:21:15:8:1, and wherein:

[0063] In the silver-containing filler, the weight ratio of micron-sized silver powder to nano-sized silver powder is 2.73:1, and the weight ratio of the sum of the weight of the micron-sized silver powder and the nano-sized silver powder, that is, the total weight of the elemental silver powder to the weight ratio of the silver-containing compound is 18.67:1;

[0064] In the organic solvent, the weight ratio of pineneol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE is 1.1:0.3:0.5:0.2, i.e. 5.5:1.5:2.5:1;

[0065] The rheological agent only includes ethyl cellulose.

[0066] Example 3

[0067] A method for preparing a silver paste composition:

[0068] The difference between this embodiment and embodiment 1 is only that the contents of the components in the obtained silver paste composition are different, specifically:

[0069] The mass of nickel powder added in step (3) was changed to 0.5 g;

[0070] The mass of the micron-sized flaky silver powder added in step (4) was changed to 5.7 g, the mass of the nano-sized spherical silver powder was changed to 1.9 g, and the mass of the silver-containing compound Ag2CO3 was changed to 0.4 g.

[0071] In the obtained silver paste composition, the weight ratio of the silver filler, the organic solvent, the non-precious metal additive, the peroxide organic additive and the rheological agent is 80:21:5:8:1, and wherein:

[0072] In the silver-containing filler, the weight ratio of micron-sized silver powder to nano-sized silver powder is 3:1.

[0073] Example 4

[0074] A method for preparing a silver paste composition:

[0075] The difference between this embodiment and embodiment 1 is only that the contents of the components in the obtained silver paste composition are different, specifically:

[0076] The amounts of the organic solvents used to form the mixed solvent in step (3) were changed to: 0.4 g of diethylene glycol butyl ether acetate, 2.1 g of terpineol, 0.8 g of diethylene glycol butyl ether, and 0.4 g of DBE to prepare the mixed solvent.

[0077] The mass of the micron-sized flaky silver powder added in step (4) is changed to 7.6 g, the mass of the nano-sized spherical silver powder is changed to 3.8 g, and the mass of the silver-containing compound Ag2CO3 remains unchanged at 0.6 g.

[0078] In the obtained silver paste composition, the weight ratio of the silver filler, the organic solvent, the non-precious metal additive, the peroxide organic additive and the rheological agent is 120:40:15:8:1, and wherein:

[0079] In the silver-containing filler, the weight ratio of micron-sized silver powder to nano-sized silver powder is 2:1.

[0080] In the organic solvent, the weight ratio of pineol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE is 2.4:0.4:0.8:0.4, that is, 6:1:2:1.

[0081] Example 5

[0082] A method for preparing a silver paste composition:

[0083] The only difference between this embodiment and embodiment 1 is that the mass of the micron flaky silver powder added in step (4) is changed to 5.6 g, and the mass of the nano spherical silver powder is changed to 5.6 g.

[0084] In the obtained silver paste composition, the weight ratio of micron-sized silver powder to nano-sized silver powder in the elemental silver powder is changed to 1:1.

[0085] Example 6

[0086] A method for preparing a silver paste composition:

[0087] The only difference between this embodiment and embodiment 1 is that the mass of the micron flaky silver powder added in step (4) is changed to 9 g, and the mass of the nano spherical silver powder is changed to 2.2 g.

[0088] In the obtained silver paste composition, the weight ratio of micron-sized silver powder to nano-sized silver powder in the elemental silver powder is changed to 4.1:1.

[0089] Example 7

[0090] A method for preparing a silver paste composition:

[0091] The only difference between this embodiment and embodiment 1 is that the diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE in step (2) are all replaced with terpineol in equal weights.

[0092] Example 8

[0093] A method for preparing a silver paste composition:

[0094] The only difference between this embodiment and embodiment 1 is that the amount of diethylene glycol butyl ether acetate in step (2) is changed to 0.1 g, and the amount of DBE is changed to 0.4 g. At this time, the weight ratio of pineol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE in the organic solvent is changed to 1.1:0.1:0.5:0.4, that is, 5.5:0.5:2.5:2.

[0095] Example 9

[0096] A method for preparing a silver paste composition:

[0097] The only difference between this embodiment and embodiment 1 is that step (1) is not performed, but 0.075 g of rheological agent ethyl cellulose, 0.025 g of rheological agent polytetrafluoroethylene wax and 0.3 g of organic solvent pineol are added to a mixed solvent prepared by 0.3 g of diethylene glycol butyl ether acetate, 0.8 g of pineol, 0.5 g of diethylene glycol butyl ether and 0.2 g of DBE to obtain a first mixed solution.

[0098] Example 10

[0099] A method for preparing a silver paste composition:

[0100] The only difference between this embodiment and embodiment 1 is that in step (1), the heating and stirring conditions for obtaining semi-finished product A are changed to 40° C., 100 min; and the heating and stirring conditions for obtaining semi-finished product B are changed to 80° C., 10 min.

[0101] Embodiment 11

[0102] A method for preparing a silver paste composition:

[0103] The only difference between this embodiment and embodiment 1 is that the first stirring condition in step (2) is changed to 800 rpm, 5 min; the second stirring condition in step (3) is changed to 1600 rpm, 0.5 min; and the third stirring condition in step (4) is changed to 2500 rpm, 1 min.

[0104] Example 12

[0105] A method for preparing a silver paste composition:

[0106] The only difference between this embodiment and embodiment 1 is that the spherical nickel powder in step (3) is replaced by spherical copper powder of equal weight and particle size.

[0107] Comparative Example 1

[0108] A method for preparing a silver paste composition:

[0109] The only difference between this comparative example and Example 1 is that no silver oxide Ag2CO3 is added.

[0110] Comparative Example 2

[0111] A method for preparing a silver paste composition:

[0112] The only difference between this comparative example and Example 2 is that no silver oxide AgO is added.

[0113] Comparative Example 3

[0114] A method for preparing a silver paste composition:

[0115] The only difference between this comparative example and Example 1 is that the mass of nickel powder added in step (3) is changed to 2 g, and the mass of micron flaky silver powder added in step (4) is changed to 3.75 g, the mass of nano-spherical silver powder is changed to 1.875 g, and the mass of silver-containing compound Ag2CO3 is changed to 0.375 g.

[0116] In the obtained silver paste composition, the weight ratio of the silver filler, the organic solvent, the non-precious metal additive, the peroxide organic additive and the rheological agent is 60:21:20:8:1, and wherein:

[0117] In the silver-containing filler, the weight ratio of the total weight of the elemental silver powder to the silver-containing compound is changed to 15:1.

[0118] Comparative Example 4

[0119] A method for preparing a silver paste composition:

[0120] The difference between this comparative example and Example 1 is that the mass of nickel powder added in step (3) is changed to 0.2 g, and the mass of micron flaky silver powder added in step (4) is changed to 10.8 g, the mass of nano-spherical silver powder is changed to 3.6 g, and the mass of the silver-containing compound Ag2CO3 remains unchanged.

[0121] In the obtained silver paste composition, the weight ratio of the silver filler, the organic solvent, the non-precious metal additive, the peroxide organic additive and the rheological agent is 150:21:2:8:1, and wherein:

[0122] In the silver-containing filler, the weight ratio of the total weight of the elemental silver powder to the silver-containing compound is changed to 24:1.

[0123] Comparative Example 5

[0124] A method for preparing a silver paste composition:

[0125] The difference between this comparative example and Example 1 is that the nano-spherical silver powder added in step (4) is replaced by an equal weight of micron-flaky silver powder.

[0126] The silver paste composition obtained at this time no longer contains nano silver powder.

[0127] Test Method

[0128] Printing effect: The silver paste compositions obtained in each embodiment and comparative example were fully stirred and uniformly mixed, and after passing through a three-roll mill and degassing, a sintered silver paste was obtained, and then printed with a steel screen with a thickness of 100 μm to obtain a printed sintered silver paste. The printing effect was then qualitatively judged by surface flatness, thickness uniformity, and whether there was solvent precipitation, and the above parameters were set to be good, average, and poor.

[0129] RBO: solvent precipitation, after printing the silver paste composition obtained in each example and comparative example, a printed pattern is obtained, and then qualitative judgment is made by microscopic observation.

[0130] Volume resistivity: The silver paste compositions obtained in each embodiment and comparative example were coated on a glass slide to form lines with a length of 50 mm, a width of 5 mm, and a thickness of 30 μm, and then placed in a 200°C oven for sintering for 60 min. After being taken out and cooled to room temperature, the resistance of the lines was measured with a low resistance tester and the volume resistivity was calculated. The resistance was less than 1×10 -5 is deemed qualified.

[0131] Bonding strength: For silver-plated substrates, (1) using a steel mesh with a thickness of 100 μm, the silver paste compositions obtained in each embodiment and comparative example were printed on the silver-plated substrate, pre-baked at 120°C, and then 5×5 SiC chips were mounted using a force of 3 kg; (2) at 260°C, a mechanical pressure of 20 MPa was applied for sintering, and the sintering time was 8 minutes to form a silver glue layer. Then, the bonding strength on the silver-plated substrate was tested by a thrust machine. For copper-plated substrates, (1) using a steel mesh with a thickness of 100 μm, the silver paste compositions obtained in each embodiment and comparative example were printed on the copper-plated substrate, pre-baked at 120°C, and then 5×5 SiC chips were mounted using a force of 3 kg; (2) at 260°C, a mechanical pressure of 20 MPa was applied for sintering, and the sintering time was 8 minutes to form a silver glue layer. Then, the bonding strength on the copper-plated substrate was tested by a thrust machine. A thrust greater than 150kg is considered qualified.

[0132] Density of the adhesive layer and the condition of holes: Taking the silver-plated substrate as an example, the chips and substrate samples that have been sintered under pressure to form a silver adhesive layer are sliced, and their cross sections are observed under a scanning electron microscope to qualitatively observe the density of the adhesive layer and the condition of holes.

[0133] The scanning electron microscope photograph of the cross section of the adhesive layer after sintering the silver paste composition obtained in Example 1 to obtain the silver adhesive layer and slicing is shown in FIG. Figure 1 (magnification is 2k) and Figure 2 (Magnification is 1k), the scanning electron microscope photo of the cross section of the adhesive layer of the silver paste composition obtained in Comparative Example 1 after sintering to obtain the silver adhesive layer and slicing is shown in Figure 3 (magnification is 3k) and Figure 4 (Magnification is 1.5k).

[0134] At the same time, regarding the density of the adhesive layer, a dense adhesive layer with no holes is considered good, otherwise it is considered poor.

[0135] The above test results are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] From the above description, it can be seen that the above embodiments of the present invention achieve good printability, low resistance after sintering, high bonding strength to silver-plated substrates and copper substrates at room temperature, and a denser product after sintering with low porosity.

[0140] Specifically, after printing, the surface is flat, the thickness is uniform, the boundaries are clear and there is no solvent precipitation; after sintering, the glue layer is dense and the porosity is low; the connection between the glue layer and the chip and the substrate is good and there is no gap; the chip thrust is greater than 160kg, and the comprehensive performance meets the chip bonding requirements.

[0141] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silver paste composition, characterized in that: The silver paste composition comprises, by weight: 80 to 120 parts of a silver-containing filler, 20 to 40 parts of an organic solvent, 5 to 15 parts of a non-precious metal additive with an atomic number of 24 to 30, 8 to 10 parts of a peroxide organic additive, and 1 to 5 parts of a rheological agent; The silver-containing filler includes elemental silver powder and a silver-containing compound, and the weight ratio of the elemental silver powder to the silver-containing compound is (18-20):1; The single substance silver powder includes micron-sized silver powder and nano-sized silver powder; The silver-containing compound is selected from one or more of silver carbonate, silver lactate, silver formate, silver citrate and silver oxide.

2. The silver paste composition according to claim 1, characterized in that The micron-sized silver powder is in the form of flakes, and the flake diameter of the micron-sized silver powder is 1 μm to 8 μm; The nano-scale silver powder is spherical, and the particle size of the nano-scale silver powder is 200nm to 500nm; Preferably, the weight ratio of the micron-sized silver powder to the nano-sized silver powder is (2-3):

1.

3. The silver paste composition according to claim 1 or 2, characterized in that: The organic solvent is selected from one or more of aromatic compounds, ketone compounds, aliphatic ester compounds, alcohol ether compounds, ether compounds, halogenated hydrocarbon compounds, diol compounds, alcohol compounds and terpene compounds; Preferably, the organic solvent is selected from one or more of terpineol, ethylene glycol monobutyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, DBE, propylene glycol monopropyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether and tripropylene glycol monopropyl ether; Preferably, the organic solvent is selected from one or more of terpineol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE; More preferably, the organic solvent is selected from a mixed solvent formed by pinene alcohol, diethylene glycol butyl ether acetate, diethylene glycol butyl ether and DBE, and in the mixed solvent, the weight ratio of the pinene alcohol, the diethylene glycol butyl ether acetate, the diethylene glycol butyl ether and the DBE is (5-6): (1-2): (2-3):

1.

4. The silver paste composition according to any one of claims 1 to 3, characterized in that The non-precious metal additive with an atomic number of 24 to 30 is copper powder and / or nickel powder; and / or, The peroxide organic auxiliary agent is selected from one or more of 1,1,3,3-tetramethylbutyl peroxyneodecanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, isopropyl peroxyneodecanoate, di-n-propyl peroxydicarbonate, tert-amyl peroxyneodecanoate and di-(3,5,5-trimethylhexanoyl)-peroxide; Preferably, the copper powder and the nickel powder are both spherical, and the particle sizes of the copper powder and the nickel powder are independently 1 μm to 5 μm.

5. The silver paste composition according to any one of claims 1 to 4, characterized in that The rheological agent is selected from one or more of methyl cellulose, ethyl cellulose, ethyl methyl cellulose, carboxy cellulose, polytetrafluoroethylene wax, polyamide wax and hydrogenated castor oil; Preferably, the rheological agent is ethyl cellulose and / or polytetrafluoroethylene wax; More preferably, the rheological agent is a mixture of ethyl cellulose and polytetrafluoroethylene wax, and the weight ratio of the ethyl cellulose to the polytetrafluoroethylene wax in the mixture is (3-4):

1.

6. A method for preparing the silver paste composition according to any one of claims 1 to 5, characterized in that: include: Step S1, mixing the rheological agent to be activated with the first organic solvent to obtain the rheological agent after activation; Step S2, mixing the rheological agent with a second organic solvent, and obtaining a first mixed solution after a first stirring; Step S3, adding the non-precious metal additive with an atomic number of 24 to 30 to the first mixed solution, and obtaining a second mixed solution after a second stirring; Step S4, adding the silver-containing filler into the second mixed solution, and obtaining a third mixed solution after a third stirring; Step S5, adding the peroxide organic auxiliary agent into the third mixed solution, and obtaining the silver paste composition after dispersion, filtration and degassing.

7. The method for preparing the silver paste composition according to claim 6, characterized in that: The activation temperature is 60° C. to 65° C., and the activation time is 30 min to 60 min.

8. The method for preparing the silver paste composition according to claim 6 or 7, characterized in that: In step S1, the weight ratio of the rheological agent to be activated to the first organic solvent is 1:(2.8-3.2).

9. The method for preparing the silver paste composition according to any one of claims 6 to 8, characterized in that: The rotation speed of the first stirring and the second stirring are independently 1000 rpm to 1400 rpm, and the time is independently 1 min to 2 min; And / or, the third stirring has a rotation speed of 1500 rpm to 2000 rpm and a duration of 3 min to 5 min.

10. Use of the silver paste composition according to any one of claims 1 to 5 as a chip packaging material in the field of electronic devices and semiconductor devices.

Citation Information

Cited By

  • Nano-silver paste for SiC semiconductor packaging, silver film, packaging structure and preparation method thereof

    CN119943473A

  • Nanoscale silver paste, silver film, packaging structure for SiC semiconductor packaging, and preparation method thereof

    CN119943473B